Prescribing of benzodiazepines among slovenian family physicians - Šubelj, Maja (Zdravstveno varstvo, 2009)
Background: In spite of their side effects, benzodiazepines are the most frequently prescribed psychotropic drugs in family medicine. The objective of this study was to investigate the possible association between physician characteristics, practice structure and practice population size with the pattern of prescribing benzodiazepines among Slovenian family physicians. Methods: We studied a representative sample of 100 family physicians using a combination of self-administered questionnaire, demographic data and data on prescribing provided by the Institute of Public Health of the Republic of Slovenia. The characteristics potentially influencing frequent prescribing were investigated by multiple linear regression analysis. Results: The estimated annual benzodiazepine consumption in Slovenia is nearly 3-fold lowerthan in the United Kingdom. Benzodiazepines were found to be less frequently prescribed by physicians with lower numbers of registered patients,as well as by female physicians, younger physicians, physicians followig the specialist training, those with short length of service, and by physicians working in large towns of the central healthcare region. The physicians'' age and access to computerised decision-making support for drug management at the workplace were found to be significantly associated with increased prescription of benzodiazepines compared to the volume of prescribed psychotropic drugs. Conclusions: The results indicate that family physicians in Slovenia prescribe appropriate amounts of benzodiazepines. Benzodiazepines are less frequently prescribed in practices with less workload, by younger and female family physicians, in practices located in central Slovenia and by family physicians with online access to information at their workplace.
Keywords: benzodiazepini; družinska medicina; predpisovanje zdravil